Resting State Functional Connectivity of the Rat Claustrum - Krimmel, Samuel R.; Qadir, Houman; Hesselgrave, Natalie; White, Michael G.; Reser, David H.; Mathur, Brian N.; Seminowicz, David A. (Frontiers in Neuroanatomy, 2019)
The claustrum is structurally connected with many cortical areas.A major hurdle standing in the way of understanding claustrum function is the difficulty in assessing the global functional connectivity (FC) of this structure. The primary issues lie in the inability to isolate claustrum signal from the adjacent insular cortex (Ins), caudate/putamen (CPu), and endopiriform nucleus (Endo). To address this issue, we used (7T) fMRI in the rat and describe a novel analytic method to study claustrum without signal contamination from the surrounding structures. Using this approach, we acquired claustrum signal distinct from Ins, CPu, and Endo, and used this claustrum signal to determine whole brain resting state functional connectivity (RSFC). Claustrum RSFC was distinct from the adjacent structures and displayed extensive connections with sensory cortices and the cingulate cortex, consistent with known structural connectivity of the claustrum. These results suggest fMRI and improved analysis can be combined to accurately assay claustrum function.